Canadian Transfer Research: Past Achievements, Current Challenges, and Future Directions - Pizarro Milian, Roger; Zarifa, David (Canadian Journal of Higher Education, 2022)
The study of transfer in Canadian post-secondary education (PSE) is a fractured terrain, with vast inter-provincial differences and deep schisms between participating communities. At the time of writing, there exists no comprehensive review of the vast, fragmented literature examining the predictors and outcomes of Canadian transfer students, thus complicating the advancement of this subfield. Through this piece, we provide a bird’s eye view of a diverse group of 100+ academic articles, policy and institutional research reports on this topic, published from 1968-2020. We use this review to trace the evolution of this complex sub-field in Canada, outlining the major findings, methodological approaches, gaps, and future challenges that Canadian researchers will face as they attempt to improve our understanding of transfer. Drawing on examples from the American and European contexts, we illustrate the need for more robust administrative data sources and methodological sophistication in Canadian transfer research. We also cite inclusive inter-sector collaboration as a key strategy to improve research in this field.